Pengembangan Media Pembelajaran Digital Storytelling Pada Materi Menulis Cerpen Siswa Kelas V SD Negeri 02 Indralaya Utara - Dea Adelia; Siti Dewi Maharani (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to develop a digital storytelling learning media for short story writing material for fifth-grade students at SD Negeri 02 Indralaya Utara. The digital storytelling learning media was developed using the ADDIE model, which includes Analyze, Design, Development, Implementation, and Evaluation. The validation results from three validators showed an average score of 94.3%, which is categorized as very valid and feasible for use. Furthermore, a practicality test was conducted by distributing response questionnaires to 20 fifth-grade students, resulting in a score of 179, with a percentage of 89.5%, which is also categorized as very practical. Thus, it indicates that the digital storytelling learning media product is appropriate for use in the learning process.